MicroRNA profiling in adults with high-functioning autism spectrum disorder - Masatoshi Nakata; Ryo Kimura; Yasuko Funabiki; Tomonari Awaya; Toshiya Murai; Masatoshi Hagiwara (Molecular Brain, 2019)
Abstract Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by social communication deficits and repetitive behaviors. Owing to the difficulty of clinical diagnosis, ASD without intellectual disability (i.e., high-functioning ASD) is often overlooked. MicroRNAs (miRNAs) have been recently recognized as potential biomarkers of ASD as they are dysregulated in various tissues of individuals with ASD. However, it remains unclear whether miRNA expression is altered in individuals with high-functioning ASD. Here, we investigated the miRNA expression profile in peripheral blood from adults with high-functioning ASD, and age and gender-matched healthy controls. We identified miR-6126 as being robustly down-regulated in ASD and correlated with the severity of social deficits. Enrichment analysis of predicted target genes revealed potential association with neurons, synapses, and oxytocin signaling pathways. Our findings may provide insights regarding the molecular clues for recognizing high-functioning ASD.